Contract for international sale of goods – Cisg its importance and applicability - Gojani, Skender; Curri, Granit (Technium Social Sciences Journal, 2021)
Contractual contests in international sale transactions mainly derive from languages, cultures, traditions, views and different legal terms of contractors in different countries worldwide. In international legal-business relations, problematic issues are inevitably outnumbered and different, thus, more difficult to be sovled. International legal-business transactions, on the other hand, are of particular importance, especially in the continuum and intences of political-economic globalization and integrations of the countries with more developed economy in different international structures such as European Union, etc. Legal regulation of sales transactions in international relations is, above all, practised with CISG, United Nations Organization Convention on International Sale of Goods which is extraordinarily important for the well-being and progress of international sales.